Improving the efficiency of methods and means for suppressing unauthorized speech recording - Oleynikov, A.N.; Pulavsky, V.A.; Chigirev, I.N. (Radiotekhnika, 2022)
The article analyzes the effectiveness of suppressing an unauthorized recording using acoustic, electromagnetic and ultrasonic countermeasures. It is shown that acoustic, electromagnetic and ultrasonic counteraction without a priori knowledge of the type of voice recorder does not provide guaranteed suppression of unauthorized speech recording. To increase the suppression efficiency, it is proposed to adapt the acoustic method, taking into account the characteristics of the propagation of acoustic vibrations in the air, the psychophysical perception of sounds by the human ear, and the use of an electrostatic emitter. The technical parameters of an electrostatic acoustic system make it possible to bring the spectral characteristics of the interference as close as possible to the voices of the interlocutors, increase the power flux density of the interference signal and reduce the intensity of its impact on the hearing organs. The article presents comparative results of experimental studies of suppressors based on adapted acoustic, electromagnetic and ultrasonic methods. The proposed adapted acoustic method for counteracting unauthorized speech recording is equally effective for any type of recording device, since the interference is generated along a functional acoustic channel, taking into account the propagation and perception of acoustic vibrations by a person.